Comparison of Long-Term Oncologic Outcomes Between Surgical T4 and T3 in Patients Diagnosed With Pathologic Stage IIA Right Colon Cancer - Jeon, Youngbae; Nam, Kug Hyun; Choi, Seok Won; Hwang, Tae Sik; Baek, Jeong-Heum (Frontiers in Oncology, 2022)
Purpose: T stage plays an important role in the classification of subgroups in stage II colon cancer. Patients with pathologic T4 are at high risk of recurrence and it is recommended to include adjuvant chemotherapy in the treatment plan, while this is not necessary in pathologic T3. There is a discrepancy between the surgical T stage (sT), as determined by the surgeon in the operative field, and pathologic T stage (pT). The pathologic stage is considered a standard prognostic factor, but it has not been established whether the surgical stage has an oncologic impact. The aim of this study was to compare oncologic outcomes between sT4 and sT3 in pathologic stage IIA right colon cancer. Methods: Between January 2005 and December 2018, there were 354 patients who underwent right hemicolectomy performed by a single surgeon (JHB) at a tertiary hospital. The data from these patients were retrospectively collected and analyzed. Only those patients with pathologic stage IIA (pT3N0M0) right colon adenocarcinomas were included in this study. Patients with mucinous carcinoma, signet ring cell carcinoma, squamous cell carcinoma, or hereditary colon cancer, and who had emergent surgery were excluded. Finally, 86 patients were included in this study. The patients were categorized, according to their surgical records, into either the sT4 group (n=28) or the sT3 group (n=58). Results: There were no statistical differences between the two groups in terms of age, sex, body mass index, comorbidities, cancer location, histologic grade, lymphovascular invasion, perineural invasion, number of harvested lymph nodes, and adjuvant chemotherapy. The 5-year overall survival rate was significantly different between the sT4 and sT3 groups (92.6 % vs. 97.7 %, p=0.024). In addition, the 5-year disease-free survival rate was significantly different between the sT4 and sT3 groups (88.6 % vs. 97.7 %, p=0.017). In the multivariate Cox regression analysis, a classification of sT4 was a significant independent predictive factor for recurrence (p = 0.023). Conclusions: Long-term oncologic outcomes have shown significant differences between surgical T4 and T3 in pathologic stage IIA right colon cancer patients. Further large-scale, multicenter studies are required to verify the clinical impact of the surgical staging.